Music therapy in neuroeducation for the learning of social skills of students with asd in an Inclusive context - Castro Ronald, Arantza (2023)
Music therapy is an alternative therapy by which music and its ele- ments  are  intended  to improve  the  quality  of  life  of  the  person, whether  physical,  social,  emotional  or intellectual. This  technique can be applied in hospitals, clinics, rehabilitation centers, and edu- cational centers, especially in children at high risk and with disabi- lities. Music is beneficial to counteract the effects of epilepsy, pain, anxiety,  recovery  and  provide  sensory balance. To  use  music  the- rapy, information must be collected from the group or person who is going to be intervened as therapeutic support, in this way it will be  possible  to  define  the  objectives  and  intervention  methods  of the planned and established sessions. Using music as a therapeutic technique  in  students  with  a  diagnosis  of Autism  Spectrum,  helps them optimize different brain areas; that will be reflected in impro- ving and activating the areas involved in learning, in psychological, social  and  behavioral  areas,  leveling  the  amount  of  neurotransmi- tters, which helps the person to stay in a state of satisfaction, rela- xation and pleasure; evidencing favorable changes in relationships with other people; in communication with their environment and in the expression of feelings, in order to be effectively included in the educational and social field.